PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH PADA PT. ASURANSI JIWASRAYA (PERSERO) DI KOTA PEKANBARU - Eliba, Fitrah; Zulkarnain, Zulkarnain (Jurnal Tepak Manajemen Bisnis, 2017)
This study aims to analyze the effect of service quality and corporate image oncustomer satisfaction PT. Insurance Jiwasraya in Pekanbaru City. To analyze theinfluence of service quality and corporate image on loyalty of PT. Insurance Jiwasrayain Pekanbaru City. To analyze the effect of customer satisfaction on customer loyaltyPT. Insurance Jiwasraya in Pekanbaru City.Population in this research is population in this research is society become individualproduct customer (polis PP) at PT. Insurance Jiwasraya in Pekanbaru City Branch asmany as 1350 people. The sample size that will be used is 140 people. Data analysisusing WarpPLS approach. WarpPLS is one of the variance-based SEM statisticalmethods designed to solve multiple regressions when specific data problems occur, suchas very small sample size, missing values and multicollinearity. PLS is an alternativeapproach that shifts from a Covarian-based SEM approach to a variance-based.The results of this study indicate that the quality of service and corporate image has aninfluence on customer satisfaction. Furthermore the quality of service and corporateimage has an influence on customer loyalty. And customer satisfaction has an influenceon customer loyalty.This research recommends PT. Asuransi Jiwasraya in Pekanbaru Branch Cityto improve the quality of service, by improving customer satisfaction that is providingservices that meet customer expectations, service quality improvement is focused on thequality of the physical environment and can be directed to strengthen customer value.